Feasibility of a pilot dyadic randomized controlled trial testing the effects of three behavioral interventions on older adults’ cognitive, physical and everyday function - Phillips, Christine B.; McVey, Ava; Tian, Junyan; Stephan, Abigail T.; Davis, W. Bennett; Aflagah, Erica L.; Ross, Lesley A. (Frontiers in Aging, 2023)
Maintaining functional abilities is critical for optimizing older adults’ well-being and independence. This randomized controlled trial (RCT) pilot examined the feasibility of testing the effects of three commercially available interventions on function-related outcomes in older adults. Pairs of community-dwelling older adults (N=55, Mage=71.4) were randomized to a 10-week intervention (cognitive-COG, physical-EX, combined exergame-EXCOG, or control-CON). Cognitive, physical, and everyday function were assessed at baseline, immediately post-intervention, and 6-months post-intervention. Feasibility was evaluated using recruitment, enrollment, training adherence, and retention metrics. Variability and patterns of change in functional outcomes were examined descriptively. A total of 208 individuals were screened, with 26% subsequently randomized. Across training arms, 95% of training sessions were completed and 89% of participants were retained at immediate post-test. Variability in functional outcomes and patterns of change differed across study arms. Results support a fully powered RCT, with several modifications to the pilot study design, to investigate short- and long-term training impacts.